2011
DOI: 10.2135/cropsci2010.06.0314
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Variation and Correlation of Seed Components in Nontransgenic Soybeans: Protein, Oil, Unsaturated Fatty Acids, Tocopherols, and Isoflavones

Abstract: The environment has a significant influence on the expression of traits contributing to soybean nutritional and/or industrial value. The aim of this study was to explore and describe the variability of nontransgenic soybean seed chemical components by investigating the environmental correlations among protein (Pr), oil (O), oleic (Ol), linoleic (La), and linolenic (Ln) acids, oleic to linolenic acid ratio (Ol:Ln) alpha‐ (AT), beta‐ (BT), gamma‐ (GT), delta‐ (DT), and total tocopherols (TT) and total isoflavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 68 publications
(94 reference statements)
5
67
3
1
Order By: Relevance
“…Yield was positively correlated with all examined constituents apart from linoleic and linolenic fatty acids and sucrose. Protein and oil exhibited a negative correlation (r = -0.25) as has been reported by Carrera et al (2011). The sum of essential and non-essential amino acids was each positively correlated with protein content, r = 0.77 and r = 0.93, respectively.…”
Section: Resultssupporting
confidence: 74%
“…Yield was positively correlated with all examined constituents apart from linoleic and linolenic fatty acids and sucrose. Protein and oil exhibited a negative correlation (r = -0.25) as has been reported by Carrera et al (2011). The sum of essential and non-essential amino acids was each positively correlated with protein content, r = 0.77 and r = 0.93, respectively.…”
Section: Resultssupporting
confidence: 74%
“…Accordingly, breeding objectives to develop soybean variety for resolving the imbalance of production and demand of soybeans are diversified with not only high yielding ability but also usability such as high functionality, and tolerance to diseases, insect pests, and stresses (Kim et al 2006). It was repoted that in spite of the same soybean variety, variations of flowering time (Kumar et al 2008), and oil and fatty acid (Shin et al 2009;Carrera et al 2011), crude protein (Kumar et al 2006), and isoflavone (Tsukamoto et al 1995;Carrera et al 2011) contents obviously occur by cultivated environmental conditions. Therefore, one of breeding strategies to achieve the goal to develop soybean varieties with high quality is the selection and application of useful soybean germplasms, which are excellent in yielding ability and principal component contents, and which are remarkably stable in agricultural traits and biochemical compositions affected by environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely documented that soybean seed composition varies with environmental factors, especially during the seed filling period when accumulation of the seed chemical components occurs (Wolf et al, 1982;Wilson, 2004;Carrera et al, 2009Carrera et al, , 2011. The relationship of protein contents (the sum of all amino acids) with temperature (Piper & Boote, 1999;Wilson, 2004) and water availability (Rose, 1988;Boydak et al, 2002;Kumar et al, 2006;Carrera et al, 2009) has also been studied, but results have shown dissimilar patterns.…”
Section: Introductionmentioning
confidence: 99%